2009
DOI: 10.1091/mbc.e09-08-0712
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Munc18-1 and -2 Double Knockdown Reveals the Essential Functions of Interaction between Munc18 and Closed Syntaxin in PC12 Cells

Abstract: Munc18-1 binds to syntaxin-1A via two distinct sites referred to as the "closed" conformation and N terminus binding. The latter has been shown to stimulate soluble N-ethylmaleimide-sensitive factor attachment protein receptor-mediated exocytosis, whereas the former is believed to be inhibitory or dispensable. To precisely define the contributions of each binding mode, we have engineered Munc18-1/-2 double knockdown neurosecretory cells and show that not only syntaxin-1A and -1B but also syntaxin-2 and -3 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
135
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 61 publications
8
135
1
Order By: Relevance
“…We previously found that Munc18-1/2 DKD causes not only a strong reduction in syntaxin-1 level but also perturbation of its plasmalemmal localization in PC12 cells (15,16). We therefore examined whether the subcellular localization of syntaxin-11 can be significantly altered by Munc18-1/2 DKD in RBL-2H3 cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We previously found that Munc18-1/2 DKD causes not only a strong reduction in syntaxin-1 level but also perturbation of its plasmalemmal localization in PC12 cells (15,16). We therefore examined whether the subcellular localization of syntaxin-11 can be significantly altered by Munc18-1/2 DKD in RBL-2H3 cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The lack of rescue by the hydrophobic pocket mutants in Munc18-2 is surprising, as we previously found that the expressions of Munc18-1 with the identical mutations showed 70-80% of the rescue ability compared with the wild type, using Munc18-1 KD and Munc18-1/2 DKD PC12 cells (15,31). Furthermore, the same (F115E) and a similar (L130K) mutant have shown a complete rescue ability in autaptic neurotransmission of Munc18-1-deficient neurons (32).…”
Section: Munc18-1 and Munc18-2 Can Effectively Support Mast Cell Degrmentioning
confidence: 88%
See 3 more Smart Citations